ATYPICAL CONGENITAL HYPERTROPHY OF THE RETINAL PIGMENT EPITHELIUM COMPLICATED BY PRESUMED RETINAL PIGMENT EPITHELIAL ADENOMA AND EXUDATIVE MACULOPATHY. Issue Volume 15:Issues 3(2021) (May 2021) - Mehta, Nitish; Gal-Or, Orly; Barbazetto, Irene; Modi, Yasha; Shields, Carol L.; Freund, K. Bailey
Abstract : Purpose: To report a retinal pigment epithelium (RPE) tumor with exudative maculopathy, originating from an atypical RPE lesion presumed to represent congenital hypertrophy of the RPE or RPE hyperplasia. Methods: Multimodal imaging including fundus autofluorescence, optical coherence tomography, fluorescein angiography, and optical coherence tomography angiography. Results: A 76-year-old West African man noted visual acuity reduction to count fingers in the right eye and 20/400 in the left eye. Features of chronic glaucoma were noted. In addition, there was a fairly well-circumscribed darkly pigmented RPE lesion in the paramacular region in the right eye, measuring 4 mm in diameter and flat and consistent with atypical congenital hypertrophy of the RPE or RPE hyperplasia. On the posterior margin of this mass was an RPE tumor, presumed to represent RPE adenoma, producing exudative maculopathy and cystoid macular edema. Multimodal imaging was used to distinguish the RPE tumor from macular neovascularization. A similar atypical congenital hypertrophy of the RPE without retinopathy measuring 3.5mm in diameter was noted in the temporal macular region in the left eye. After six monthly doses of intravitreal bevacizumab (1.25 mg/0.05 mL) in the right eye, the maculopathy resolved and the RPE mass showed partial involution with visual acuity return to baseline 20/200. Conclusion: Congenital hypertrophy of the RPE and RPE hyperplasia can produce RPE adenoma with related exudative maculopathy. In this case, the maculopathy responded to bevacizumab. Abstract : A 76-year-old man was found to have exudative maculopathy caused by a retinal pigment epithelium tumor originating from atypical congenital hypertrophy of the retinal pigment epithelium that later responded to intravitreal bevacizumab.